Childhood Asthma-Management Practices in Rural Nigeria: Exploring the Knowledge, Attitude, and Practice of Caregivers in Oyo State - Oyindamola Akinso; Atin Adhikari; Jingjing Yin; Joanne Chopak-Foss; Gulzar Shah (MDPI AG, 2023)
Background: Caregivers of asthmatic children have a poor knowledge of proper asthma-management practices in Nigeria. This study examined the knowledge, attitudes, and practice behaviors of caregivers in the management of asthma in children under 5 years of age in Oyo State, Nigeria. Methods: While a mixed method was used in the original research, this brief describes the quantitative method used in this study to evaluate caregivers' asthma-management practices. A 55-item questionnaire on childhood asthma knowledge, attitude, and practice was administered during child welfare-clinic visits to 118 caregivers. Data were analyzed using the IBM SPSS Version 25.0. Statistical significance was set at p < 0.05 and 95% CI. Result: More than 70% of caregivers knew that asthma is associated with airway inflammation and about 90% knew that flu infections triggered asthma attacks in their children. Caregivers with a higher income (OR = 3.0; 95% CI = 1.558-5.778; p = 0.001) were 3.0 times more likely to practice proper asthma-care behavior than those with a lesser income. Conclusions: Childhood asthma remains underdiagnosed and undertreated in Nigeria. An optimal public health approach is needed to identify and target underserved communities that suffer poorer asthma outcomes and to improve caregivers' knowledge and practices of asthma management.